PENINGKATAN HASIL BELAJAR BAHASA INGGRIS POKOK BAHASAN MAKNA DALAM TEKS LISAN FUNGSIONAL MELALUI STRATEGI TRUE OR FALSE PADA SISWA TUNANETRA KELAS VII DI SLB-A TPA JEMBER - Arida Choirun Nisa (Program Studi Pendidikan Luar Biasa Universitas PGRI Argopuro Jember, 2022)
This study aims to improve learning outcomes in class VII English students on the subject of meaning in functional oral texts through the True or False Strategy in SLB-A (Blind) TPA Jember in the 2013/2014 academic year. This study used a classroom action research design (CAR). The subject of this classroom action research is the subject of English, the subject matter of the Meaning in Functional Oral Texts by applying the True or False learning strategy, in class VII SLB-A (Blind) TPA Jember, with a total of 2 students. The research was conducted in two cycles, cycle I on July 2 - July 9 2013, cycle II on July 16 - July 29, 2013 and adjusted to the schedule of activities. The result of this research is that learning with the True or False strategy has a positive impact in improving the results of learning English about the meaning in functional oral texts for seventh grade students of SLB-A (blind) TPA Jember. This can be seen in Cycle I, from 2 students who have completed 1 student (50%) and 1 student (50%) who have not completed. Whereas in Cycle II, all students have completed (100%). So, after Cycle II student learning outcomes increased by 50%.